Genome-Wide identification and salt stress-responsive expression dynamics of the HMGR gene family in Ziziphus jujuba var. spinosa. - Xiaohan Tang; Xiaojun Ma; Jun Cao; Xinhong Wang; Xuexiang Li; Xiaozhou Yang; Jing Shu (PLoS ONE)
Terpenoids are critical components of plant environmental adaptation mechanisms. They also exhibit significant therapeutic potential in herbal medicine. 3-Hydroxy-3-methylglutaryl coenzyme A reductase (HMGR), a pivotal rate-limiting enzyme governing the initial stage of the mevalonate (MVA) pathway in triterpene saponin biosynthesis, remains uncharacterized in Ziziphus jujuba var. spinosa. Through genome-wide and molecular analysis, we systematically identified ZjHMGR isoforms and revealed differential tissue-specific expression patterns and significant salt stress-responsive regulation across identified isoforms. Our findings reveal three evolutionarily conserved ZjHMGR isoforms with a complete HMG-CoA reductase domain and closely related to Populus trichocarpa. Collinearity analysis revealed two collinear gene pairs, and purifying selection was identified as the primary evolutionary force acting on the ZjHMGR gene family. Cis-acting element analysis revealed that ZjHMGR gene family enriched MYB-related, TC-rich repeats, light- and hormone-responsive elements, suggesting transcriptional regulation by environmental stimuli and phytohormones. Spatiotemporal expression analysis via qRT-PCR revealed differential transcriptional patterns of ZjHMGR members, with pronounced upregulation under ABA, MeJA, and light induction. Saline stress disrupted the growth of wild jujube seedlings while activating ZjHMGR expression alongside other MVA pathway genes. Overexpression of ZjHMGR enhances salt stress resistance in Arabidopsis thaliana. This study lays the foundation for further investigations into the molecular mechanisms of the ZjHMGR gene family concerning saponin biosynthesis, phytohormone interactions, and salt tolerance in wild jujube.